Eye movement control in reading unspaced text: the case of the Japanese script - Kajii, Natsumi; Nazir, Tatjana A.; Osaka, Naoyuki (Vision research (Oxford), 2001)
The present study examines the landing-site distributions of the eyes during natural reading of Japanese script: a script that mixes three different writing systems (Kanji, Hiragana, and Katakana) and that misses regular spacing between words. The results show a clear preference of the eyes to land at the beginning rather than the center of the word. In addition, it was found that the eyes land on Kanji characters more frequently than on Hiragana or Katakana characters. Further analysis for two- and three-character words indicated that the eye's landing-site distribution differs depending on type of the characters in the word: the eyes prefer to land at the word beginning only when the initial character of the word is a Kanji character. For pure Hiragana words, the proportion of initial fixations did not differ between character positions. Thus, as already indicated by Kambe (National Institute of Japanese Language Report 85 (1986) 29), the visual distinctiveness of the three Japanese scripts plays a role in guiding eye movements in reading Japanese.